2019
DOI: 10.1515/opag-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of serious gaming – the case of “The Maladaptation Game”

Abstract: The use of digital tools and interactive technologies for farming systems has increased rapidly in recent years and is likely to continue to play a significant role in meeting future challenges. Particularly games and gaming are promising new and innovative communication strategies to inform and engage public and stakeholders with scientific research. This study offers an analysis of how a research based game on climate change maladaptation can support, but also hinder players’ sense-making processes. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…This demonstrates the trade-off between the wish to address several complexities and to disseminate clear messages about the value of measures. Balancing simplification and complexity is a common challenge for climate change games, and in line with earlier studies [6,7,20,26]. This also points to the importance of not using games as a stand-alone event but as an integrated part of a longer learning process [31,36].…”
Section: Discussionsupporting
confidence: 63%
“…This demonstrates the trade-off between the wish to address several complexities and to disseminate clear messages about the value of measures. Balancing simplification and complexity is a common challenge for climate change games, and in line with earlier studies [6,7,20,26]. This also points to the importance of not using games as a stand-alone event but as an integrated part of a longer learning process [31,36].…”
Section: Discussionsupporting
confidence: 63%
“…An assessment of the game from a communication theoretical perspective (Asplund et al, 2019) identified a number of opportunities and barriers that to some extent resonate with the current literature on serious gaming. In this section, we expand upon this analysis with reference to comments and feedback collected during the gaming sessions.…”
Section: Engagement Interactivity and Experienced Relevancementioning
confidence: 82%
“…The Maladaptation Game was designed to support dialogue to better understand how agricultural actors make decisions regarding adaptation as they simultaneously have to consider potential maladaptive outcomes (http://maladaptationgame.info/). The games was found to both support and hinder players' sense-making processes around climate change maladaptation in various ways [Asplund et al, 2019]. In a study design similar to this one, focus group participants' perspectives on the benefits and challenges of playing The Maladaptation Game were analysed.…”
Section: Methodsmentioning
confidence: 99%